2021
DOI: 10.3390/children8040282
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Language Delay among Healthy Preterm Children, Language Outcomes and Predictive Factors

Abstract: Language delay (LD) and its relationship with later language impairment in preterm children is a topic of major concern. Previous studies comparing LD in preterm (PT) and full-term (FT) children were mainly carried out with samples of extremely preterm and very preterm children (sometimes with additional medical problems). Very few of them were longitudinal studies, which is essential to understand developmental relationships between LD and later language impairment. In this study, we compare the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
4
4
0
1
Order By: Relevance
“…Furthermore, Faiçal et al [ 10 ] and Mulkey et al [ 11 ] already described decreased neurodevelopmental scores over time on ZIKV prenatally exposed children without microcephaly at birth. We present a rate of mild neurodevelopmental disorders (4/150 (2.6%)) similar to the prevalence described in our region [ 21 ] and other studies on Spanish and worldwide populations [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Faiçal et al [ 10 ] and Mulkey et al [ 11 ] already described decreased neurodevelopmental scores over time on ZIKV prenatally exposed children without microcephaly at birth. We present a rate of mild neurodevelopmental disorders (4/150 (2.6%)) similar to the prevalence described in our region [ 21 ] and other studies on Spanish and worldwide populations [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results of the ANOVA are quite clear, and no significant differences were found between the PT and the FT groups, although the FT children show slightly higher results in all the measures taken except in word understanding at 10 months, sentence complexity at 22 months and in word production, regular suffixes and sentence complexity at 30 months of age. This indicates that the performance of the PT children seems to improve relatively as they grow older, supporting previous findings, because PT children obtain relatively better results when compared to FT children at 30 months of age ( Gayraud and Kern, 2007 ; Pérez-Pereira, 2021 ). The fact that prematurity correction for age has been used may be behind these findings, since correction for age is less pertinent, and may have a higher effect, at 30 months of age than at 10 and 22 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…We also found that exposure at a later stage of development was less detrimental to language skills, implying that advanced age might be protective. This is confirmed by previous studies that reported age as a protective factor for early language delay [ 39 , 40 ]. There is evidence that parental screen duration can, directly and indirectly, affect children’s screen duration and the parent-child relationship [ 41 ].…”
Section: Reviewsupporting
confidence: 91%